Penatalaksanaan Holistik Pada Ibu Rumah Tangga Dengan Carpal Tunnel Syndorme (CTS) Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Kebon Jahe - Aurelina, Renata; Angraini, Dian Isti (Medula, 2024)
Carpal tunnel syndrome (CTS) is a syndrome that arises due to neuropathic pressure on the median nerve in the carpal tunnel at the wrist which is precisely under the flexor retinaculum. Risk factors for CTS include obesity, sedentary wrist activity, pregnancy, genetic heredity, and rheumatic inflammation. So that proper treatment is needed and carried out holistically with a family medicine approach to achieve therapeutic success. Application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient-centered and family problem-solving framework. Primary data were obtained through anamnesis, physical examination, supporting examinations and home visits to assess the physical environment. Patient Mrs. S, 49 years old, came with complaints that the thumb, index finger and middle finger of the right hand felt numb and stiff since one month ago. The patient is worried that the complaint will worsen and interfere with activities. The patient was clinically diagnosed with CTS (ICD-10 G56.0). Furthermore, management, intervention and evaluation are carried out. On evaluation, there were reduced complaints, increased patient knowledge about the disease and changes in behavior in the position of doing daily homework. After carrying out holistic and comprehensive management, patients experience an increase in knowledge about their disease. Complaints of numbness and stiffness in the patient's right hand are reduced, the patient and his family do homework in the right way and position.